2021
DOI: 10.1002/fsn3.2159
|View full text |Cite
|
Sign up to set email alerts
|

A novel process to improve the characteristics of low‐fat ice cream using date fiber powder

Abstract: The objective of this study was to improve the characteristics of low‐fat ice cream (LFIC) using date fiber powder (DFP). DFP was added to LFIC mix (3% fat, 14% milk solids nonfat, 15% sucrose, 0.3% stabilizer, and 0.1% vanilla) at a rate of 1.5%, 2.5%, and 3.5%. Control treatment with no DFP was also manufactured for comparison. The LFIC mix was analyzed for physicochemical and microbiological analyses. After manufacture, microbiological, rheological, and sensory characteristics of LFIC were evaluated during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The iodine value ( AOAC, 2000 ; method 993.20), saponification number ( AOAC, 2000 ; method 920.160), and soluble volatile fatty acids ( AOAC, 2000 ; method 960.30) were also determined in extracted fat from fat products and hard cheese. The total bacterial count (TBC) was determined as described in other studies ( Hammam et al, 2018 ; Ahmed et al, 2021 ; Hamdy et al, 2021 ; Kamel et al, 2021b ; a ; Mansour et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The iodine value ( AOAC, 2000 ; method 993.20), saponification number ( AOAC, 2000 ; method 920.160), and soluble volatile fatty acids ( AOAC, 2000 ; method 960.30) were also determined in extracted fat from fat products and hard cheese. The total bacterial count (TBC) was determined as described in other studies ( Hammam et al, 2018 ; Ahmed et al, 2021 ; Hamdy et al, 2021 ; Kamel et al, 2021b ; a ; Mansour et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Akalın et al [49] reported that dietary fibers obtained from orange, apple, and wheat provided a significant increase in overrun values compared to the control sample. On the other hand, Mansour et al [50] reported that the addition of datary fiber powder significantly reduced the overrun value of the ice cream samples. Some researchers have suggested that there is a relationship between the overrun value and the rheological properties [6,26].…”
Section: Overrun Properties Of Ice Creammentioning
confidence: 99%
“…Total count of psychrotrophic bacteria was enumerated using the SPC technique and incubated cultured plates for 10 days at 7°C (Mansour et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%